Perbandingan Status Kesehatan Gingiva pada Pengguna Kontrasepsi Oral dan Suntik di Kecamatan Belik Kabupaten Pemalang - Wulansari, Fatwa Maulida, Dwi Kurniawati, S.KG, MPH, drg. Fitria Nur Malita Sari (2015)
Background : Hormonal contraception was kind of birth control method. It consists of oral and injection methods. Oral contraception contain progesterone. Thus women who use hormonal contraception will increace steroid hormones (estrogen, progesteron, endogenous) on their body which will cause gingival inflammation. Aim : Their study was aimed to understand the effect of oral and injection contraception usage toward gingivalis status at subdistrict Belik, Pemalang. Methode: It was clinical observational study with cross sectional approach. Respondent consisted of 82 women between 19-35 year old at Belik Pemalang, who already used oral and injection contraception for more than one year. Gingival Status were measured using Gingival Index Loe and Silness (1963). The data were then analyzed using Mann Whitney test with 95% significant level. Result : The result showed that there was an effect of oral and injection contraception usage towards Gingival Status between two study groups proved with p value p=0,000(P<0,05). Conclusion: women with oral contraception has worse Gingival Status than the ones using injection method.